Augustyn z Hippony: „urząd miłości” - Kaczmarek, Tomasz (Vox Patrum, 2016)
The expression found in the paper’s title that originates from the Treatise on the Gospel of John is an illustration of the program of Augustine’s pastoral service, focusing on his great love of the Church. Indeed, whenever the bishop of Hippo was undertaking any ecclesiological issue, the theme of his love of the Church was always evident too. The Church, although tainted by human weakness, is for any Christian, a unique boat that heads safely towards the „fatherland”. It is a love of the Church where a man’s answer to the love of God is both clearly audible and visible. The paper aims to show some parts of that love. Firstly by referring to the process of Augustine’s personal discovery of the Church, and secondly to mention some significant events from his heroic seeking for the good of the Lord’s flock in the light of his fidelity to the entrusted to him amoris officium.